Konseptualisasi Peran Strategis pada Pendidikan Literasi Keuangan Syariah Anak Melalui Pendekatan Systematic Review di TK RA Al-Mu’min Gunung Putri - Amalia Nabila; Abrista Devi; Indriya Indriya (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
Children have good potential so that they can develop through interaction activities with the surrounding environment. Children can also determine Islamic financial products and services according to their needs, understand the benefits and risks, understand their rights and obligations, and believe that the selected service products can improve children's welfare in accordance with Halal principles and are profitable. Sharia law. Islamic financial literacy, meaning knowledge, skills and beliefs that can influence and improve the quality of financial management decisions to achieve prosperity. with faith, morality, and sharia. This study aims to comprehensively analyze the appropriate role of the relevant parties. The research method conceptually explores the strategic role of various related parties in the development of Islamic financial literacy education among early ages. Sources of information varied with interviews and utilized additional information as logical examination articles, books and applicable reports. The examination is calculated by the systematic review method. Children need Islamic financial literacy education because they need support and direction from each of the four conceptual strategic roles in order to achieve Islamic financial literacy from an early age.